Transmissão de cepas de Candida spp entre pacientes HIV positivos e seus contatos domiciliares - Antunes, Fabíola Assad (2011)
Household transmission of Candida spp isolates is a little discussed topic in the medical literature, though transmission in the nosocomial enviroment and between sexual partners is already well stablished. The subjects in our study were divided into the following groups: HIV-positive patients with oral candidiasis (Group 1), HIV-positive patients colonized by isolates of Candida spp in the oral cavity (Group 2) and a control group, comprised of HIVnegative blood donors (Group 3) and their respective household contacts, in a total of 343 subjects. Data were obtained regarding age, sex, previous exposure to azoles, previous history of oral candidiasis, HIV sorology, HIV viral load, CD4 cell count, tabagism, denture use, sexual partner status and other imunossupressive underlying conditions from the subjects; the recovered isolates were phenotipically tested for species differentiation and were submitted to antifungal drugs susceptibility tests. Among the HIV-positive patients, assymptomatic oral Candida spp. carriage rate was 34,3%, and among the HIV-negative subjects the rate was 19,3%; there was no statistical difference between the two groups. Using multivariate analysis, HIV infection was the only risk factor associated with assymptomatic oral Candida spp cariage. Multivariate analysis was also employed to evaluate risk factors associated with oral candidiasis; age was the only identified risk factor. Among the HIV-positive patients, though, CD4 count below 200 was also associated with oral candidiasis; the same did not occur with high HIV viral load. The most prevalent species was Candida albicans (77,98%), and 14,7% of the isolates were azole-resistant or DDS. Most of the resistant isolates belonged to Group 1. The simultaneous isolation of 46 strains of Candida albicans, wich belonged to 22 households, were submitted to RAPD, using the primers M2 and RP-2. The RAPD results did not show any correlations between the same household strains, but showed a relationship between strains obtained from subjects who lived within no geographical proximity, showing that the technique employed had no discriminatory power for genotyping the involved strains.